2017
DOI: 10.1016/j.ahj.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Use of troponin assay 99th percentile as the decision level for myocardial infarction diagnosis

Abstract: Background The Universal Definition of Myocardial Infarction recommends the 99th percentile concentration of cardiac troponin in a normal reference population as part of the decision threshold to diagnose type 1 spontaneous myocardial infarction. Adoption of this recommendation in contemporary worldwide practice is not well known. Methods We performed a cohort study of 276 hospital laboratories in 31 countries participating in the National Heart, Lung, and Blood Institute sponsored International Study of Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 17 publications
0
27
0
3
Order By: Relevance
“…The use of high-sensitivity cardiac troponin assays and lowering the diagnostic threshold to the 99th centile remains a contentious issue in clinical practice; 5 therefore, despite guideline recommendations, 1 few institutions worldwide have adopted high-sensitivity assays. 6 , 7 If increased sensitivity does not affect the specificity of testing for the diagnosis of myocardial infarction, then introducing high-sensitivity assays will improve patient outcomes through better targeting of therapies for coronary heart disease. However, if the increase in sensitivity leads to poor specificity, then patients could be misdiagnosed, given inappropriate medications, and potentially have adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of high-sensitivity cardiac troponin assays and lowering the diagnostic threshold to the 99th centile remains a contentious issue in clinical practice; 5 therefore, despite guideline recommendations, 1 few institutions worldwide have adopted high-sensitivity assays. 6 , 7 If increased sensitivity does not affect the specificity of testing for the diagnosis of myocardial infarction, then introducing high-sensitivity assays will improve patient outcomes through better targeting of therapies for coronary heart disease. However, if the increase in sensitivity leads to poor specificity, then patients could be misdiagnosed, given inappropriate medications, and potentially have adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…47 Hip fracture is an ideal condition for international comparative research because diagnosis is relatively simple and admission to hospital is standard practice in the developed world. 54 Thus, unlike with conditions such as pneumonia, joint arthroplasty or even myocardial infarction, for which patients may (or may not) seek medical care, 26,[55][56][57] patients with hip fracture tend to be comparable across geographic regions, and selection effects are minimal. 11,58 Although geographic variations in care are well described within countries, 59,60 cross-border research is much more limited.…”
Section: Openmentioning
confidence: 99%
“…This has been demonstrated across the 276 hospital laboratories contributing to the ISCHEMIA trial, where 1 in 4 sites reported decision thresholds more than 5-fold greater than manufacturer recommendations, with the majority using contemporary cardiac troponin assays. 13 It is clear that variation also exists in the adoption of sex-specific diagnostic thresholds, despite evidence of potential benefit to reduce the under-recognition of myocardial infarction in women. 14,15 This may reflect dominance of the high-sensitivity cardiac troponin T assay which, until its U.S. approval, has not recommended sex-specific cut-off values.…”
Section: Global Variation In the Selection Of Assay And Diagnostic Thmentioning
confidence: 99%